Newer drug delivery systems in anesthesia - Sona Dave; Deepa Shriyan; Pinakin Gujjar (Wolters Kluwer Medknow Publications, 2017)
A paradigm shift in drug delivery systems have been noted recently.The focus nowadays is to obtain maximum benefit with lower side effects.It is a monetary burden to launch newer molecules hence the industry is concentrating on improving the efficacy of existing molecules. Thus controlled release, target controlled infusion and closed loop infusion have entered the scene. Applying pharmacokinetic principles, instead of mathematically calculating drug dose could improve safety and maintain steady drug levels in the body. When computers are applied to an efficient operating system, it will only magnify the efficiency. Most of these technologies which were earlier limited to research only have entered clinical practice. This has made it mandatory for the practicing clinician to familiarize themselves with these technologies. Our focus in this review has been to discuss newer drug delivery systems available for anesthesiology practice.